2009
DOI: 10.1002/rcm.4097
|View full text |Cite
|
Sign up to set email alerts
|

Is there any 12C/13C fractionation during starch remobilisation and sucrose export in potato tubers?

Abstract: The delta(13)C (carbon isotope composition) variations in respired CO(2), total organic matter, proteins, sucrose and starch have been measured during tuber sprouting of potato (Solanum tuberosum) in darkness. Measurements were carried out both on tubers and on their growing sprouts for 23 days after the start of sprout development. Sucrose was slightly (13)C-depleted compared with starch in tubers, suggesting that starch breakdown was associated with a small isotope fractionation. In sprouts, all biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…leaflet replenishment), a rapid transition occurred with a 13 C-depletion of OM and an increase in chlorophyll content; and (iii) autotrophic leaves were 13 C-depleted suggesting they were mainly using photosynthates. Our results also confirmed the 13 C-depletion in autotrophic tissues (leaflets) compared to heterotrophic ones (rachis and petiole) already reported for other species, 16 but we showed huge changes during leaf development. The present results on the use of the carbon isotope composition for investigating the leaf growth and development at plant scale for oil palm open new insights into the carbon metabolism and allocation studies of other sink organs such as trunk, roots and bunches.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…leaflet replenishment), a rapid transition occurred with a 13 C-depletion of OM and an increase in chlorophyll content; and (iii) autotrophic leaves were 13 C-depleted suggesting they were mainly using photosynthates. Our results also confirmed the 13 C-depletion in autotrophic tissues (leaflets) compared to heterotrophic ones (rachis and petiole) already reported for other species, 16 but we showed huge changes during leaf development. The present results on the use of the carbon isotope composition for investigating the leaf growth and development at plant scale for oil palm open new insights into the carbon metabolism and allocation studies of other sink organs such as trunk, roots and bunches.…”
Section: Discussionsupporting
confidence: 94%
“…Another hypothesis is that adult autotrophic leaves (source) supplied carbon to young heterotrophic leaves with photosynthetic carbohydrates originally 13 C-depleted, which were then enriched in 13 C during remobilisation and transportation, as suggested by many authors. 11,15,16,24 Fructose was also believed to participate in leaf growth: its concentration in heterotrophic leaves was higher (from 3 to 7 mg g À1 DW) than that of other sugars. It might also participate through important translocation, perhaps from the first 12 autotrophic leaves to the leaves under elongation.…”
mentioning
confidence: 98%
“…However, Bathellier et al . (2008) and Maunoury‐Danger et al . (2009) demonstrated that during ontogeny of Phaseolus vulgaris L. seeds and during sprouting of Solanum tuberosum tubers sucrose export was not associated with fractionation.…”
Section: Discussionmentioning
confidence: 98%
“…Considering the more general concept of carbon sources versus carbon sinks, another interesting study can be added for comparison. Maunoury‐Danger et al . (2009) found that when sprouting occurs in Solanum tuberosum tubers in the dark, sucrose δ 13 C in the heterotrophic sprouts (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation